Proteomic analysis of Buffalo milk somatic cells reveals metabolomic and immunological transitions during early lactation - Priyanka M. Kittur; Lija Satheesan; Narasimha Tanuj Gunturu; Yallappa M. Somagond; A. P. Madhusoodan; Ravi Kumar Gandham; Rani Alex; Ajay Kumar Dang (Scientific Reports)
Abstract Buffalo milk is renowned for its nutritional and functional properties. Milk somatic cells protect the mammary gland, contribute to the functionality of the udder, and also aid in the health and development of newborn calves, particularly during the critical early lactation period. However, proteomic changes in buffalo milk somatic cells during the transition from colostrum to mature milk remain poorly understood. This study was formulated to characterize the proteomic dynamics of buffalo milk somatic cells using Liquid chromatography-tandem mass spectrometry (LC-MS/MS) during colostrum-to-mature milk transition and to reveal shifts in metabolic and immune functions. A total of 4,429 high-confidence proteins were identified in the colostrum and milk of buffaloes. Up-regulated proteins [Padj<0.05, log2(Fold change, FC) ≥ 1.5] across different days of sampling were involved in metabolism of sugars, lipids, and amino acids, pentose-phosphate pathway, insulin-signaling, biosynthesis of amino acids and cofactors, and ubiquitin-proteasome system. Down-regulated proteins [Padj<0.05, log2(FC) ≤ 0.5] were associated with lipid transport, aldosterone synthesis and secretion, mineral balance, complement-coagulation system, antigen processing and presentation, and mRNA processing. A notable shift in hub proteins was detected, and selected ones were validated by real-time qPCR. These findings highlight significant changes in the proteome profile, biological functions, and specific pathways in milk somatic cells during early lactation in buffaloes. In conclusion, milk somatic cells contribute not only to mammary immunity but also to the nutritional support of the growing calf.